2009
DOI: 10.3800/pbr.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Symbionts of marine medusae and ctenophores

Abstract: Abstract:Since marine medusae and ctenophores harbor a wide variety of symbionts, from protists to fish, they constitute a unique community in pelagic ecosystems. Their symbiotic relationships broadly range from simple, facultative phoresy through parasitisim to complex mutualism, although it is sometimes difficult to define these associations strictly. Phoresy and/or commensalism are found in symbionts such as pycnogonids, decapod larvae and fish juveniles. Parasitism and/or parasitoidism are common in the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 66 publications
0
46
0
4
Order By: Relevance
“…Large jellyfish can harbor a wide variety of symbionts such as dinoflagellates, cnidarians, helminths, crustaceans, ophiuroids and fishes (Mansueti 1963, Thiel 1970, 1978, Arai 1997, Purcell & Arai 2001, Ohtsuka et al 2009. However, their symbiotic interactions are highly diversified, ranging from phoresy through parasitoidism to mutualism (Ohtsuka et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large jellyfish can harbor a wide variety of symbionts such as dinoflagellates, cnidarians, helminths, crustaceans, ophiuroids and fishes (Mansueti 1963, Thiel 1970, 1978, Arai 1997, Purcell & Arai 2001, Ohtsuka et al 2009. However, their symbiotic interactions are highly diversified, ranging from phoresy through parasitoidism to mutualism (Ohtsuka et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Large jellyfish can harbor a wide variety of symbionts such as dinoflagellates, cnidarians, helminths, crustaceans, ophiuroids and fishes (Mansueti 1963, Thiel 1970, 1978, Arai 1997, Purcell & Arai 2001, Ohtsuka et al 2009. However, their symbiotic interactions are highly diversified, ranging from phoresy through parasitoidism to mutualism (Ohtsuka et al 2009). We have been intensively investigating symbioses between jellyfish and other organisms in Asian waters since 2008, and found that juveniles of the shrimp scad Alepes djedaba (Forsskål) is widely associated with many species of large jellyfish in tropical Asian waters (Ohtsuka et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…During nematocyst discharge, venom-filled tubules explosively penetrate the cuticle of the prey (Tardent & Holstein 1982, Purcell 1984 and inject their venom through the tubules (Lotan et al 1996, Yanagihara et al 2002. Despite the potency of venom in jellyfish, phyllosomas of spiny (Palinuridae) and slipper (Scyllaridae) lobsters often associate with gelatinous zooplankton, including jellyfish (Booth et al 2005, Ates et al 2007, Ohtsuka et al 2009, O Rorke et al 2014. Indeed the phyllosomas of Ibacus novemdentatus Gibbes, 1850 (Decapoda: Achelata: Scyllaridae) have been reported to ride and prey on cnidarian jellyfish in the wild (Shojima 1963).…”
mentioning
confidence: 99%
“…Seus volumosos corpos com estruturas como braços orais e pórticos genitais, oferecem micro ambientes onde vivem peixes juvenis (Ohtsuka et al, 2009), caranguejos (Nogueira Jr. & Haddad, 2005), tremátodes Nogueira Jr et al, 2014) e camarões (Martinelli Fº et al, 2008).…”
Section: Introdução Geralunclassified
“…Esses simbiontes buscam proteção contra predadores, parasitam as medusas, ingerem suas presas e outros simbiontes (Ohtsuka et al, 2009). Mais recentemente, especulouse que organismos simbiontes e predadores de gelatinosos, poderiam estar aumentando juntamente com o aumento de populações de gelatinosos (Utne-Palm et al, 2010).…”
Section: Introdução Geralunclassified